A progressive Method for Solving recursive equations -- Difference Equation Method

Source: Internet
Author: User
    • A progressive Method for Solving recursive equations -- Difference Equation Method
A progressive Method for Solving recursive equations -- Difference Equation Method

Here, we only consider the following:

T(N) =C1T(N-1) +C2T(N-2) +... +CKT(N-K) +F(N),NK(6.18)

. WhereCI (I = l, 2 ,...,K) Is a real constant, andCK = 0. It can be rewritten to a linear constant coefficient.KNon-homogeneous differential equations:

T(N)-C1T(N-1 )-C2T(N-2 )-... -CKT(N-K) =F(N),NK(6.19)

(6.19) Linear Constant CoefficientKThe structures of non-homogeneous ordinary differential equations are very similar, so the solutions are similar. Due to space limitations, the solution (6.19) is provided here, And the correctness proof is omitted.

Step 1, Calculate the homogeneous equation corresponding to (6.19:

T(N)-C1T(N-1 )-C2T(N-2 )-... -CKT(N-K) = 0 (6.20)

The basic solution is to write the feature equation (6.20:

C(T) =TK-C1TK-1-C2TK-2 -... -CK = 0 (6.21)

IfT=RIs (6.21) m heavy root, then (6.20) m base solutionRN,NRN,N2RN ,...,NM-1RN; ifP EIθ andP e-I θ is a pair of (6.21)LFor a duplicate common root, 2 of (6.20) is obtained.LBasic solutionsPNCOs,PNsin,N PNCOs,N PNsin,...,NL-1PNCOs,NL-1PNCOs. In this way, you can obtain all the roots of (6.21 ).K. BesidesK(6.20. That is, any solution of (6.20) can be expressed as thisKLinear Combination of basic solutions.

Step 2, For a special solution of (6.19. In theory, the special solution of (6.19) can be obtained by using the Laplace constant variation method. However, it is very troublesome to use explicit expressions of (6.20) general solutions, that is, linear combinations of (6.20) basic solutions. Therefore, in practice, the test method is often used, that is, based onF(N) Characteristics of the speculative form of special solutions, leave a number of adjustable constants, the speculative solution generation (6.19) and then determine. Due to the particularity of (6.19), the superposition principle can be usedF(N) Is linearly decomposed into the sum of several individual items, and corresponding special solutions of each individual item are obtained.F(N. This makes the test method more effective. For convenience, three special formsF(N), And the corresponding special solutions (6.19) are listed in Table 6-1, which can be applied directly. WherePI, I = 1, 2 ,..., S is a constant to be determined.

Table 6-1 Common special solutions for Equations (6.19)

F ( n ) format parts special solution form of equation (6.19)
A n C ( A ) =0
A is C ( T ) m of
n S C (1) = 0
1 is C ( T ) m of
n S A n C ( A ) =0
A is C ( T ) m of

Step 3Write (6.19), that is, the general solution of (6.18 ).


{TI (N), I = 0, 1, 2 ,...,N} Is the basic solution of (6.20,G(N) Is a special solution for (6.19. Then, by the initial condition (6.18 ),

T(I) =TI, I = 1, 2 ,...,K-1

To determine the undetermined composite constant in (6.22 {AI}, that is, Linear Equations


Solve {AAnd return (6.22 ). WhereβJ =TJ-G(J),J= 0, 1, 2 ,...,K-1.

Step 4, The approximate order of the estimated (6.22) is the requirement.

The following are two examples.

Example LRecursive equation

Its corresponding feature equation is:

C(T) =T2-T-1 = 0

We can solve the problem by using two single sums. The basic solution for the corresponding (6.20) is {R0n,R1n }. A special solution for (6.19) isF*(N) =-8, so the corresponding (6.19) call is:

F(N) =A0R0n +A1R1n-8

To meet the initial conditions, the second-order linear equations are obtained:



And thus



Example 2Recursive equation

T(N) = 4T(N-1)-4T(N-2) + 2NN(6.23)

And initial conditionsT(0) = 0,T(1) = 4/3.

Its corresponding feature equation (6.21) is

C(T) =T2-4T+ 4 = 0

There is a dual RootR= 2. Therefore, the basic solution for (6.20) is {2n, 2nN }. BecauseF(N) = 2nN, using Table 6-1, a specific solution of the corresponding (6.19) is

T*(N) =N2 (P0 +P1N) 2N,

Generation (6.23)P0 = 1/2,P1 = 1/6. Therefore, the corresponding (6.19) call is:

T(N) =A02n +A1N2n +N2 (1/2 +N/6) 2N,

Make it meet the initial conditionsA0 =A1 = 0, thus

T(N) =N2 (1/2 +N/6) 2N

ThereforeT(N) =θ(N32n ).

Contact Us

The content source of this page is from Internet, which doesn't represent Alibaba Cloud's opinion; products and services mentioned on that page don't have any relationship with Alibaba Cloud. If the content of the page makes you feel confusing, please write us an email, we will handle the problem within 5 days after receiving your email.

If you find any instances of plagiarism from the community, please send an email to: info-contact@alibabacloud.com and provide relevant evidence. A staff member will contact you within 5 working days.

A Free Trial That Lets You Build Big!

Start building with 50+ products and up to 12 months usage for Elastic Compute Service

  • Sales Support

    1 on 1 presale consultation

  • After-Sales Support

    24/7 Technical Support 6 Free Tickets per Quarter Faster Response

  • Alibaba Cloud offers highly flexible support services tailored to meet your exact needs.